2019
DOI: 10.1093/mnras/stz451
|View full text |Cite
|
Sign up to set email alerts
|

Brangäne: a new family of Barbarian asteroids

Abstract: The so-called Barbarian asteroids (from the name of the prototype of this class, asteroid (234) Barbara) are extremely interesting objects because they might be the survivors of a very early generation of planetesimals. We have identified in the past the first case of an asteroid family (the Watsonia family) whose members are Barbarians, all issued from the collisional disruption of a sizeable parent body. Here we report on the identification of another family, called after the name of its biggest member, aste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The authors also concluded that the presence of CAIs is responsible for the abnormal polarimetric inversion angle of the Barbarians. In this respect, Barbarians could be among the oldest main-belt asteroids, containing the samples of the oldest solid materials found in the Solar system (Sunshine et al 2008;Cellino et al 2019).…”
Section: Connection With Barbarian Asteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also concluded that the presence of CAIs is responsible for the abnormal polarimetric inversion angle of the Barbarians. In this respect, Barbarians could be among the oldest main-belt asteroids, containing the samples of the oldest solid materials found in the Solar system (Sunshine et al 2008;Cellino et al 2019).…”
Section: Connection With Barbarian Asteroidsmentioning
confidence: 99%
“…Recently, Kuroda et al (2021) identified the first Barbarian asteroid in the NEO population. The main known reservoirs of these objects are the Watsonia (Cellino et al 2014) and Brangane (Cellino et al 2019) asteroid families. While the origin of Kamo'oalewa in the high-inclination Watsonia family (Novaković et al 2011) seems unlikely, it might be arriving from the Brangane family via the 3:1 mean motion resonance with Jupiter (see Table 2).…”
Section: Connection With Barbarian Asteroidsmentioning
confidence: 99%
“…In addition, polarimetric studies of these objects (to probe explosion symmetries) require the highest possible polarisation precision. • Solar system transients 21 and interstellar interlopers 22 : the study of comets, asteroids and visits from interstellar objects. Again, instrumental requirements are the highest possible throughput and the highest possible polarisation precision.…”
Section: Science Goalsmentioning
confidence: 99%
“…Ito et al 2018). More than two dozen objects in the main-belt asteroids, including candidate objects, belong to the first group (Cellino et al 2019). The group name "Barbarians" comes from the name of the first discovered asteroid (234 Barbara).…”
Section: Introductionmentioning
confidence: 99%
“…Sunshine et al (2008) suggested that some of these asteroids possessed the so-called calcium aluminum-rich inclusion (CAI) from their near-infrared spectral characteristics, and their corresponding meteorites were of CV class, such as the Allende meteorite. Barbarians have only been found within main-belt asteroids larger than 40-50 km in diameter, with the exception of the possible members of the Watsonia and Brangäne families (Cellino et al 2019).…”
Section: Introductionmentioning
confidence: 99%